Non-volatile low-power crossbar memcapacitor-based memory. (June 2017) - M. Emara, Ahmed A.; Aboudina, Mohamed M.; Fahmy, Hossam A.H.
Abstract: This paper proposes the use of a memcapacitor as a new memory cell. This new element may lead to a better memory on many directions: non-volatility, speed, density, and power consumption. To the best of our knowledge, we present the first Verilog-A model for memcapacitors and use it to simulate the memory cell then complete crossbar arrays of various sizes. The reading circuits completely solve the sneak paths problem including the effect of coupling parasitics in the large arrays. Our analysis indicates that memcapacitor memories are non-volatile memories with a density at least equivalent to dynamic RAMs but with lower power consumption.